Literaturas e infâncias: pesquisa (d)e pós-graduação como espaço político - Maria Amélia Dalvi (Estudos de Literatura Brasileira Contemporânea)
This work reviews the theses published by Brazilian universities from 1987 to 2012 that focus on the relationships between literature and childhood. The aim is to understand what can be learned from either the reiterated presence or the glaring absence of certain themes, questions, references, methods and conclusions. We believe that such investigation allows us to track the “achievements” and “challenges” that those dedicated to study the relations between literature and childhood have to face. By that, we can consider postgraduate studies/research as a political space where culture is produced in the relations between literature and childhood.